Ultra‐fast LC–MS/MS in therapeutic drug monitoring: Quantification of clozapine and norclozapine in human plasma. Issue 2 (19th July 2017) - Couchman, Lewis; Fisher, Danielle S.; Subramaniam, Krithika; Handley, Simon A.; Boughtflower, Robert J.; Benton, Christopher M.; Flanagan, Robert J.
Abstract : A novel approach to high‐throughput, targeted liquid chromatography–tandem mass spectrometry (LC–MS/MS) analysis has been developed. A single chromatographic system can be used for the analysis of a range of 20 drugs and metabolites with a total analysis time of 36 s (one 96‐well plate of prepared samples per hour). To demonstrate the applicability of this approach to quantitative analysis, a method has been validated for the therapeutic drug monitoring of clozapine and norclozapine following automated extraction from human plasma. Chromatographic retention times were 11.4 and 12.4 s for norclozapine and clozapine, respectively (for both analytes the chromatographic peak width was less than 1 s). Comparison with a conventional LC–MS/MS method (5 min analysis time) showed excellent agreement. This new approach offers analysis times more akin to flow‐injection analysis, but is likely to be more widely applicable because of chromatographic resolution from residual matrix components and isobaric interferences. Abstract : A novel approach to ultra‐rapid, high‐throughput LC–MS/MS analysis has been developed. The total analysis time was just 36 s per injection, or one 96‐well plate of prepared samples per hour, for the demonstrated application of clozapine and norclozapine analysis in human plasma samples. This approach is simple, and is likely to be ideally suited to a number of targeted assays.